Enhancing nutritional and sensory properties of plant-based beverages: a study on chickpea and Kamut® flours fermentation using Lactococcus lactis - Mefleh, Marina; Omri, Ghofrane; Limongelli, Rosangela; Minervini, Fabio; Santamaria, Monica; Faccia, Michele (Frontiers in Nutrition, 2024)
The study aimed to set up a protocol for the production of a clean-label plant-based beverage (PBB), obtained by mixing chickpeas and Kamut® flours and using a commercial Lactococcus lactis (LL) as fermentation starter, and to characterize it, from nutritional, microbiological, textural, shelf-life, and sensory points of view. The effect of using the starter was evaluated comparing the LL-PBB with a spontaneously fermented beverage (CTRL-PBB). Both PBBs were high in proteins (3.89/100 g) and could be considered as sources of fiber (2.06/100 g). Notably, L. lactis fermentation enhanced the phosphorus (478 vs. 331 mg/kg) and calcium (165 vs. 117 mg/kg) concentrations while lowering the raffinose content (5.51 vs. 5.08 g/100 g) compared to spontaneous fermentation. Cell density of lactic acid bacteria increased by ca. two log cycle during fermentation of LL-PBB, whereas undesirable microbial groups were not detected. Furthermore, L. lactis significantly improved the beverage’s viscosity (0.473 vs. 0.231 Pa s), at least for 10 days, and lightness. To assess market potential, we conducted a consumer test, presenting the LL-PBB in “plain” and “sweet” (chocolate paste-added) variants. The “sweet” LL-PBB demonstrated a higher acceptability score than its “plain” counterpart, with 88 and 78% of participants expressing acceptability and a strong purchase intent, respectively. This positive consumer response positions the sweet LL-PBB as a valuable, appealing alternative to traditional flavored yogurts, highlighting its potential in the growing plant-based food market.